Tradisi Gugur Gunung adalah praktik budaya yang dilakukan oleh masyarakat pedesaan - Afriska Mita Ardani (Studi Administrasi Publik dan ilmu Komunikasi, 2024)
Traditions that contain noble values ​​such as closeness, unity and orientation towards common interests are increasingly disappearing from people's lives. This research uses a qualitative approach by collecting data through observation, in-depth interviews and documentation. An evolutionary theoretical framework is used to understand the observed reality. This study concludes that changes in agricultural land ownership, the involvement of the village government in the process, as well as village development budget allocations which reduce community independence, are the main factors in the decline and disappearance of the mountain autumn tradition. The impact extends to the economic, social and cultural fields.